Molecular engineering of bandgaps in covalent organic frameworks - Li, Xing (2020)
Two-dimensional (2D) covalent organic frameworks (COFs) are an emerging class of porous materials with potential for wide-ranging applications. Intense research efforts have been directed at tuning the structure and topology of COF, however the bandgap engineering of COF has received less attention, although it is a necessary step for developing the material for photovoltaic or photonic applications. Herein, we have developed an approach to narrow the bandgap of COFs by pairing triphenylamine and salicylideneaniline building units to construct an eclipsed stacked 2D COF. The ordered porous structure of 2D COF facilitates a unique moisture-triggered tautomerism. The combination of donor–acceptor charge transfer and tautomerization in the salicyclidineaniline unit imparts a large bandgap narrowing for the COF and turns it color to black. The synthesized COF with donor–acceptor dyad exhibits excellent nonlinear optical properties according to open aperture Z-scan measurements with 532 nm nanosecond laser pulses.